Analisis Manajemen Global Ti Untuk Meningkatkan Efisiensi Dan Pendapatan - Anggun Rohaya Putri Munthe; Juliya Arma; Nidaul Husna; Nurbaiti Nurbaiti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The research results show that the implementation of global IT through cloud computing, data integration, business process automation, and standardized IT governance can significantly improve operational efficiency. Furthermore, IT utilization also contributes to increased revenue through innovation of digital products and services, improved customer service quality, and accelerated international market expansion. However, global IT implementation faces several challenges such as data security, regulatory differences, and the digital competency gap. The development of information technology (IT) in the digital era has encouraged companies to implement IT management on a global scale to improve operational efficiency and expand revenue potential. This study aims to analyze how a global IT management strategy can be implemented effectively and how it impacts organizational efficiency and revenue. The research method uses a qualitative approach with literature review techniques and content analysis of various journals, company reports, and relevant scientific publications. This study concludes that global IT management is a strategic factor that can strengthen a company's competitiveness in global competition. Integrated, adaptive IT management that is aligned with business objectives has been proven to drive efficiency, innovation, and sustainable revenue growth.